Statins: Evidence for effectiveness - K. Outhoff (South African Family Practice)
Since their introduction in 1987, statins have become the largest-selling prescription drugs worldwide, and have kept both the scientific and lay press captivated. There were reports this year alone that statins may prevent hysterectomies in women with fibroids, are linked to better health outcomes after brain haemorrhage, may protect against the microvascular complications of diabetes, as well as against cerebral reperfusion injuries, may lower the risk of Barrett’s oesophagus, alter the inflammatory response to the common cold, slow the progression of advanced multiple sclerosis, and offer added benefit to men with erectile dysfunction.1 Amid this hype and against a backdrop of more the a billion people potentially taking statins,11 the obvious question is whether or not current evidence on the safety and efficacy of statins still overwhelmingly favours these agents for their licensed indication of lowering cholesterol and preventing cardiovascular disease morbidity and mortality.